Pengaruh Personal Selling dan Word of Mouth terhadap Keputusan Pembelian Pestisida Toko Wahyu Tani - Oktaviani, Karina; Talkah, Abu; Arisyahidin, Arisyahidin (Universitas Islam Kadiri, 2025)
Agriculture plays a crucial role in food security, particularly in food provision. One major challenge faced by farmers is pest and disease attacks that threaten crop yields. Pesticides are widely used to mitigate these threats. Agricature Store Wahyu Tani, a pesticide retailer operating for over 30 years, provides various pesticide products from well-known brands. Amid increasing competition, the store continues to adapt, relying on personal selling and word-of-mouth (WOM) strategies to influence farmers' purchasing decisions. This study examines the impact of personal selling and WOM on pesticide purchasing decisions at Agricature Store Wahyu Tani. Using purposive sampling, 60 customers were surveyed through questionnaires. Multiple linear regression analysis reveals that both personal selling and WOM positively influence purchasing decisions, both individually and simultaneously. The result of the analysis using IBM SPSS Statistic 27 showed the R-square value of 0.780 indicates that 78% of the variability in purchasing decisions is explained by these variables. The linier regression analysis result of Y = 6.325 + 0.641X1+ 0.402X2 and the The F-value (100.883) > F-table (3.16).